Strengthening the Performance of Samoa's Fruit and Vegetable Sector - World Bank (Washington, DC, 2013)
Numerous opportunities exist to improve the performance of Samoa's fresh fruit and vegetable (F&V) sector. Current per capita consumption appears to be low by regional and global standards indicating prospects for future demand growth and a need for increased awareness of the dietary benefits of fruit and vegetable consumption. A large share of the existing demand for fruits and vegetables is being met by imports and there appears to be scope for encouraging domestic production to reduce Samoa's import dependence. The presence of well-organized retail and foodservice channels represent a considerable advantage to an organized fresh produce supply chain, provided that domestic producers are able to meet buyer standards for product continuity, quality and price. There are several products which could also be developed into sustainable export commodities. A range of on-farm investments, training, organizational and research priorities have been identified to enable the F&V sub-sector to respond to these potential market opportunities. Following an appraisal of opportunities and an analysis of value chains for representative commodities which might be grown in response to demand from the local market, the report recommends a series of proposed actions to strengthen the performance of the fruit and vegetable sub-sector in Samoa.